Ion reflection by shock waves and pulse generation by cross-field ion beams. (4th January 2017) - Ohsawa, Yukiharu
Abstract : Comparisons are made of two different particle simulations: one for the study of plasma-based accelerators (Gueroult & Fisch, Phys. Plasmas, vol. 23, 2016, 032113) and the other for the study of shock formation in the interstellar medium (Yamauchi & Ohsawa, Phys. Plasmas, vol. 14, 2007, 053110). In the former, shock waves used for plasma density control create ion beams by reflection. In the latter, a fast and dense beam of exploding ions penetrates a surrounding plasma. In both simulations, magnetic bumps are generated from the motion of ion beams perpendicular to a magnetic field. Despite the apparent differences of their purposes, configurations and spatial scales, the two simulations show strong similarities in the generation processes and effects of the bumps, suggesting that these are not rare plasma phenomena. The bump created by the exploding ions develops into backward and forward magnetosonic pulses.